2020
DOI: 10.1016/j.heliyon.2020.e04481
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-cancer efficacy and phyto-chemical screening of solvent extracts of Kigelia africana (Lam.) Benth

Abstract: Background and objectives Kigelia africana is a medicinal plant growing naturally in many parts of Africa. In Kenya, a water concoction of the plant is used to treat breast and prostate cancers. Laboratory data on its anti-cancer activity and active principles is limited, hence no scientific rationale for its medicinal use. This study reports on in-vitro toxic activities of dichloromethane and methanol extracts of the plant against human breast cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…A binary solvent system was used; solvent A (water with 0.1% formic acid); and solvent B (methanol with 0.1% formic acid) at a flow rate of 7 mL/min 4 . 3 , 9 The run was monitored at 30 min. The identification of the chromatographic peaks was performed using addition of compound isolated in the previous step.…”
Section: Methodsmentioning
confidence: 99%
“…A binary solvent system was used; solvent A (water with 0.1% formic acid); and solvent B (methanol with 0.1% formic acid) at a flow rate of 7 mL/min 4 . 3 , 9 The run was monitored at 30 min. The identification of the chromatographic peaks was performed using addition of compound isolated in the previous step.…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic drugs and antibiotics cure many microbial and viral infections caused by biofilm-forming bacteria and viruses, which is of main public health concern. 1,2 Allopathic medicines mostly tend to develop patentable compound “magic bullet,” which may evoke sensitivity and other allergic responses. Moreover, chemotherapeutic drugs to date also impose toxic effects on other non-target tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, chemotherapeutic drugs to date also impose toxic effects on other non-target tissues. 2 In contrast, medicinal plants employed to heal the illness and restore equilibrium by converging on specific biomolecules and pathways. 2 These natural remedies have been developed overages through extensive experimentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benth. (Wambua Mukavi et al, 2020 ), Diospyros kaki leaves (Ko et al, 2020 ), Licorice (Wang, Luo, et al, 2019 ), Phoenix dactylifera L. (Khan et al, 2017 ), germ and bran of red rice (Upanan et al, 2019 ), Coptis chinensis (Kim et al, 2021 ), and Juniperus communis Linn. (Huang et al, 2021 ), have been found to induce the apoptotic death of HepG2 cells via the exogenous, mitochondria‐mediated endogenous pathway, MAPK signaling pathway, and ER signaling pathway.…”
Section: Introductionmentioning
confidence: 99%